Komodifikasi Konten dan Khalayak Youtube dalam Penayangan Situational Comedy “Lapor Pak! Edisi Kiky Saputri Roasting Ganjar Pranowo” - Riyantie, Mayang; Rusadi, Udi (Jurnal Publisitas, 2024)
The purpose of this research is to reveal the phenomenon of content and audience commodification in the situational comedy (sitcom) "Lapor Pak! Kiky Roasting Ganjar Pranowo Edition," which is broadcast on the Trans7 Official YouTube platform. In this situation, political content has been transformed into entertainment that utilizes roasting techniques, political innuendo, and satirical humor to elicit emotions and audience participation. This research uses a critical paradigm and qualitative approach with content analysis methods and comments columns on the YouTube Trans7 Official platform. This research reveals how content creators are aware of the emotional influence and opinions of viewers as a valuable asset in increasing the popularity of their shows. The research results note that content creators use content commodification tactics by converting political issues into entertaining entertainment, resulting in feelings of controversy and high audience interaction. On the other hand, audiences are not only passive consumers, but also data producers who contribute in the form of comments, reactions and opinions which become economic value for the media. This data not only reflects a show's popularity, but is also used to measure the success of content within the social media marketplace. The results of this research highlight the importance of the interaction between content commodification and audiences in the context of the political economy of media. This phenomenon reflects the transformation of media from a source of information to a commodity that relies on audience participation and emotions. The conclusion is that content creators have succeeded in turning political issues into entertainment that provokes the audience's emotions. Audiences are not only consumers, but also data producers through their comments and reactions, which have economic value for the media. The results of this research not only reflect the popularity of the show, but also serve as a measure of the success of the content. This emphasizes the importance of the interaction between content commodification and audiences in the transformation of media into commodities depending on the audience's participation and emotions.